PENGARUH SIZE, OPERATING CYCLE DAN ACCRUAL RELIABILITY TERHADAP EARNING PERSISTANCE - Saputra, Wendy Salim; Wong, Natasya; Loanza, Marshia (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
Profit plays a very important role as an indicator for evaluating company performance. Profit information will not be useful if it is not of good quality. The more a company can produce quality profit information, the more it will reflect the company's sustainability, financial condition and performance in the future. Quality profits are profits that contain predictive value, which is one aspect of relevance in fundamental quality, which is the ability of accounting information to be used as a basis for estimating future figures. The level of profit persistence can describe the influence of current year profits on future profits. The basis for the calculation is core earnings, so that the profits presented in the report are profits that are relevant to the company's routine operational processes and are not the result of transitory or extraordinary income items. Profit persistence can also describe what level of income the company can maintain in each operational period. The higher the profit persistence, the better the company is at maintaining their income level.The aim of this research is to obtain empirical evidence regarding the influence of sales volatility, cash flow volatility and debt levels on profit persistence. This research will then use multiple regression analysis starting with descriptive statistical testing, classical assumption testing and hypothesis testing. This research was conducted on cyclical and non-cyclical consumer sector companies in 2020 - 2022. The results of this research show that size has a negative effect on earnings persistence, operating cycle has a positive effect on earnings persistence, while accrual reliability has no effect on earnings persistence.